DO REMITTANCES âMAKE ITâ FOR THEIR MEMBERS LEFT BEHIND? URBAN TO RURAL REMITTANCES BY MIGRANTS IN FOUR INDONESIAN CITIES - Effendi, Tadjuddin Noer (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2015)
This paper examines the nature, extent, and effect of remittances sent by urban migrants to home villages.Â More specifi cally it examines: the magnitude of remittances, type and background of migrants sendingÂ remittance, the extent of remittances sent, and the use of remittances. This study is carried out in fourÂ major cities in Indonesia that have experienced signifi cant infl ows of ruralâurban migrants over the pastÂ few decades: Tangerang in Banten, Samarinda in East Kalimantan, Medan in North Sumatra and MakassarÂ in South Sulawesi. Using survey data collected in 2008-2009, this study found that, over time, rural-urbanÂ migrants have an opportunity to save portion of their income that subsequently send the remittances out toÂ home village. Rural-urban migrants seem need time to be older and reach a certain level of income beforeÂ they begin to send remittance. Statistically, age is among personal backgrounds that have signifi cant effectÂ on propensity to send or not send remittances. One of important social dimensions of rural-urban migrationÂ in many developing countries is its effect on household members, particularly household members orÂ children left behind. This does not seem to be the case in four cities under study, where many urban-ruralÂ migrants are accompanied by their members (wives and children).